In vivo models of human articular cartilage mechanosensitivity - Mündermann, Annegret; Liphardt, Anna-Maria; Herger, Simon (Elsevier, 2023)
Mechanical load is important for the development, maintenance, and regeneration of healthy musculoskeletal tissues, including articular cartilage. Elucidating the association between mechanical load applied to articular cartilage and changes in articular cartilage metabolism in the context of articular cartilage health will not only allow evaluating the role of mechanical loading in the pathophysiology of diseases affecting articular cartilage but also broaden the understanding of the effects of mechanical loading on joint health or their role in fostering articular cartilage regeneration after injury. In this chapter, we provide a critical overview of existing human in vivo models for articular cartilage mechanosensitivity. The material is based on studies investigating the response of biochemical markers of articular cartilage health to acute stimuli and interventions, including loading stress, immobilization, microgravity, and medical interventions, in healthy and pathological populations.
CRIS-Team Scopus Importer:2023-11-24
Keywords: exercise; human model; In vivo; joint load; stress test; tissue metabolism